SUAS working conditions in the context of the COVID-19 pandemic - Rizzotti, Maria Luiza Amaral; Magalhães , Jaciana Moura; Vieira , Maria do Socorro Souza (Argumentum, 2021)
This article offers an interpretation of working conditions within the Unified Social Assistance System (SUAS), and especially changes caused by the COVID-19 pandemic. The data employed is the result of a survey carried out by the Socio-Assistance Monitoring Management of the nine north-eastern states, and we focus on results portraying the state of Paraíba. Our analysis recognizes that the structural conditions of Brazilian workers are marked by inequalities of social class, race and gender and sheds light on the specificities of work in the social assistance sector. Our findings particularly highlight enrolment, salaries, objective working conditions and changes in the current situation, profoundly aggravated, as it is, by the largest pandemic of the 21st century.